From Molecular Mechanisms to Clinical Strategies: A Comprehensive Overview of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) - Damian Świerczek; Maja Dreger; Jakub Jatkowski; Jakub Kancerek; Bogna Drozdzowska; Romuald Wojnicz (International Journal of Molecular Sciences, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), has become one of the most common chronic liver diseases worldwide, representing a major global health challenge closely linked to metabolic syndrome, obesity, and type 2 diabetes mellitus (TD2M). The condition is characterized by a multisystem nature driven by complex multifactorial mechanisms, including insulin resistance, lipotoxicity, mitochondrial dysfunction, genetic predispositions, and gut-liver axis alterations. Although liver biopsy remains the gold standard, non-invasive markers and advanced imaging methods are of key importance for early risk stratification. Furthermore, while liver-related complications such as fibrosis, cirrhosis, and hepatocellular carcinoma (HCC) are significant, cardiovascular disease remains the leading cause of mortality in patients with MASLD. Current management relies primarily on lifestyle modifications, targeted pharmacotherapy (such as pioglitazone, GLP-1 receptor agonists, SGLT-2 inhibitors), and novel experimental therapies. Consequently, MASLD requires a multidisciplinary approach emphasizing early diagnosis, risk stratification, and comprehensive treatment of both hepatic and extrahepatic manifestations.